Project Based Learning (PjBL) Learning Model to Train The Pedagogical Competencies of Prospective Science Teacher Students - Astriani, Dyah; Fauziah, An Nuril Maulida; Hendratmoko, Ahmad Fauzi; Rosdiana, Laily; Martini, Martini (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2025)
Pedagogical competence is very necessary to improve the learning process. Pedagogical competency is a competency that prospective science teachers must have. This relates to the duties of teachers who are not only teachers, but also as educators and mentors of students. Prospective teachers need to have both academic and non-academic competencies. This research aims to analyze the pedagogical competence of prospective teachers in terms of their ability to prepare learning plans. The method used by researchers in this research is a project with a quantitative approach. The research results show that prospective science teacher students are able to design learning by implementing innovative learning models, utilizing relevant technology, with the hope of making it easier for students to understand the learning material